Distinguishing abstract from concrete concepts in supramodal brain regions. (August 2019) - Gao, Chuanji; Baucom, Laura B.; Kim, Jongwan; Wang, Jing; Wedell, Douglas H.; Shinkareva, Svetlana V.
Abstract: Concrete words have been shown to have a processing advantage over abstract words, yet theoretical accounts and neural correlates underlying the distinction between concrete and abstract concepts are still unresolved. In an fMRI study, participants performed a property verification task on abstract and concrete concepts. Property comparisons of concrete concepts were predominantly based on either visual or haptic features. Multivariate pattern analysis successfully distinguished between abstract and concrete stimulus comparisons at the whole brain level. Multivariate searchlight analyses showed that posterior and middle cingulate cortices contained information that distinguished abstract from concrete concepts regardless of feature dominance. These results support the view that supramodal convergence zones play an important role in representation of concrete and abstract concepts. Highlights: We investigated the neural correlates of differences between concrete and abstract concepts. We were able to successfully identify individual trials as abstract or concrete based on whole brain activity patterns. Posterior and middle cingulate cortices were shown to contain information for distinguishing concrete and abstract concepts. Supramodal convergence zones play an important role in representation of concrete and abstract concepts.